Strategi Entrepreneurial Marketing dalam Meningkatkan Daya Saing pada UMKM Melisa Mart - Najwa Hanum Ramadhani; Hadi Ismanto (PT. Alahyan Publisher Sukabumi, 2026)
This study aims to analyze the implementation of Entrepreneurial Marketing strategies in increasing competitiveness in MSMEs in Melisa Mart. The research uses a qualitative approach with a case study method to gain an in-depth understanding of the application of entrepreneurship-based marketing strategies in MSME business activities. Data collection was carried out through observation, in-depth interviews, and documentation, while informant selection was conducted using purposive sampling techniques. The validity of the data was tested through source triangulation and triangulation techniques, then analyzed using the Miles, Huberman, and Saldaña interactive model which included data condensation, data presentation, and conclusion drawn. The results of the study show that Melisa Mart MSMEs have implemented seven dimensions of Entrepreneurial Marketing, namely proactiveness, opportunity focus, innovation orientation, calculated risk taking, customer intensity, resource leveraging, and value creation. The dimensions of customer intensity and value creation are the most dominant factors in increasing competitiveness because they are able to build customer loyalty and create added value through responsive service and product quality that suits consumer needs. In addition, the use of digital media, service innovation, and optimization of resources also strengthen the adaptability of businesses to changes in the business environment. The integrated implementation of Entrepreneurial Marketing has been proven to be able to increase the competitiveness of Melisa Mart MSMEs through strengthening relationships with customers, creating innovations, efficient resource utilization, and being able to respond quickly to market opportunities. This research is expected to be a reference for MSME actors in developing adaptive, innovative, and value-creation-oriented marketing strategies to achieve sustainable competitive advantage.